Fire safety system in old folk home / Syafinaz Ghani - Ghani, Syafinaz (Faculty of Architecture, Planning and Surveying, 2014)
Fires are one of cause’s people deaths and fire also is important for people doing daily activities in the home. Without fires people can’t do their daily activity. For the methodology from the research involved literature review the process of data collection get from of the respondents by questionnaire surveys and interview session at the old folk home case studies in Klang, Selangor From the research, it can see the mostly old folk home just provide some fire protection equipment like fire extinguisher, fire sprinkler, fire alarm and means escape, the critical problem of a fires, the fire safety management are the fire drill at the old folk home users how to save self; the perform of fire and fire drill procedures; that take time to clear a house because mostly elderly in home can’t move quickly and in provide clear signage indicating exit routes and location of fire safety equipment. The one of the best way to prevent fire in of old folk home with to save that flammable materials in a safe area and To prevent that continuous the people in old folk cook avoid wearing loose fitting clotting with this material can easily catch on fire and also that never leave kitchen while cooking without supervision even for a short time, to give awareness for users this reach will provide some useful insight on the important aspects of fire safety in management and proper methods are fire protection system, and thus, help guide old folk home users to safeguard both their life and property. From management home must provide for uses and to ensure that there are have clear or “glow in the dark “signage indicates exit routes and location of fire safety equipment.